PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PRODUK MAKANAN YANG TIDAK MEMILIKI SERTIFIKASI HALAL DI KOTA PEKANBARU - Fendra Rizaldy Pratama; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
So far, both food products in the form of raw and ready-to-eat ingredients and drinks with a varietyof flavors and colors have been circulating widely on the market. The number of circulating productsrequires strong control from the government and related parties to ensure that food products on the marketmeet the proper standards and labeled halal for consumption. Therefore, consumers have the right to getinformation about the product content, ingredients made and halal products. will be consumed.This type of research can be classified in the type of sociological (empirical) legal research, becausein this study the authors directly conduct research at the location or place of study in order to provide acomplete and clear picture of the problem under study. This research was conducted research in PekanbaruCity. The reason the author chose the research location in Pekanbaru is because there are still manybusiness actors who have not included a halal label on the goods being traded. While the population andsample are the Chairperson of the Indonesian Ulema Council (MUI) of Riau Province, PekanbaruBreadtalk Employees and Pekanbaru Breadtalk Consumers. Data sources used are primary data andsecondary data. Data collection techniques in this study were interviews, questionnaires, and literaturereview.The conclusions that can be obtained from the results of the study are: First, the factors underlyingthe producers who do not carry out halal certification of their products in the city of Pekanbaru consist ofignorance and lack of understanding of business actors regarding the existence of Law Number 33 of 2014concerning Halal Product Guarantee, Actors Businesses Not Knowing the Procedures for Registering HalalCertification, Businesses that are Goed by Business Actors are still on a Small Business scale, Businessactors assume that the raw materials used in products are Halal, business actors or producers are dishonestand commit fraud or fraud to consumers and the level of public knowledge about halal label food productsis still low. Second, legal protection for consumers of products that do not have halal certification in the cityof Pekanbaru is not yet maximally implemented. This is indicated by the fact that there are still manyproducts that do not yet have certification and have not been labeled as halal. In addition, the emergence offake halal labels that do not meet the criteria for halal or not.Keywords: Legal Protection, Consumer, Food Products, Halal Certification, Pekanbaru